Serviços de visualização de dados em bibliotecas de pesquisa: diretrizes para a elaboração de um modelo de implementação para o Brasil - (:unkn) unknown (INSTITUTO BRASILEIRO DE INFORMAÇÃO EM CIÊNCIA E TECNOLOGIA / UNIVERSIDADE FEDERAL DO RIO DE JANEIRO, 2024)
Research libraries, as providers of information and support services for scientific research, have become a suitable means of retraining their users by encouraging the development of multiple skills aimed at understanding, visualizing and analyzing data. Librarians have a fundamental role to play in supporting scientists and introducing them to tools and services that help them process the data collected or produced by these researchers in their respective research. In this context, data can be generated in abundance by means of instruments or computer simulations, and processed with the help of efficient software. This makes it absolutely necessary to engage in new activities and approaches to deal with the storage, access, analysis, visualization and preservation of data resulting from scientific research. With this in mind, it is hypothesized that it is possible to propose the successful implementation of data visualization services in Brazilian research libraries through effective training and collaboration strategies, in order to overcome these barriers, even in the face of significant budget limitations, challenges related to the renewal of the activities performed and the training of librarians. The aim of this study was to analyze the processes related to implementation, skills acquisition and mediation resulting from the provision of data visualization services in research libraries. In order to achieve this objective, the research had both exploratory and descriptive characteristics. The first was used in the initial part of the thesis - the most theoretical - where the deductive method was applied to carry out a bibliographical survey and a systematic literature review. The second part - the descriptive part - used the inductive method to record and describe facts, particularities and relationships present in the population under investigation. To this end, a survey was carried out in the form of a questionnaire with all the libraries in the sample and a case study with a field trip to the United States for an interview and observation based on non-participant observation in some selected institutions. As a result of the research, it was possible to identify a variety of data visualization services offered by libraries that deal with research data.The categories established included support, training, tools, information resources, infrastructure and events, covering a wide range of practices and approaches. The analysis showed that the successful adaptation of these services to Brazilian libraries depends on the implementation of effective strategies, taking into account the available infrastructure and the specific demands of users. US libraries stand out for their integrated approach, which involves everything from technical support to training events. It was observed that the success of these services is directly linked to the continuing education of librarians and inter-institutional collaboration, essential elements for meeting contemporary technological and information demands. The adaptation of the best practices observed in the United States to the Brazilian context was central to the development of a flexible model, which can be applied to different types of research libraries, as long as it is properly adjusted to their particularities. The research concluded that the implementation of data visualization services in Brazilian libraries is feasible, provided that effective training and collaboration strategies are adopted, and that these services have the potential to promote scientific advancement and innovation in the country.
Keywords: Serviço de visualização de dados; Bibliotecário de dados; Biblioteca de pesquisa; Multicompetências; Múltiplas competências; Competência em visualização de dados; Ciência da Informação; Data visualization service; Data librarian; Academic library; Multiskills; Data visualization literacy; Information Science; Ciência da informação